The hundred secret senses - Tan, Amy (New York : Ivy Books, 1996)
Chinese-American Olivia Laguni's life is changed by her nemesis and half-sister, Kwan Li, whose haunting predictions and implementation of the secret senses link their family's struggles to the challenges of their ancestors.
Keywords: Chinese American women -- Fiction; Domestic fiction